Penentuan Konsentrasi Larutan Koh Terbaik Pada Saponifikasi Stearin Hasil Pengolahan Minyak Sawit Kasar Di Mini Plant Politeknik Kampar Menghasilkan Sabun Dan Gliserol - Fatmayati Fatmayati; Nur Asma Deli (Politeknik Kampar, 2019)
Politeknik Kampar as an educational institution based palm oil industry has a mini plant processing crude palm oil plant with a capacity of 700 kg / batch which produces olein and stearin. Stearin until now still not processed and utilized in order to bring economic value. The research purposes were to examine the use of stearin to produce soap and glycerol, knowing the best concentration of KOH solution on the process of saponification of palm oil stearin and produces soap and glycerol in consistent with ISO related. The preliminary research was conducted to determine whether stearin can be saponified in order to produces soap and glycerol.